FREQUENCY OF AWARENESS IN MOTHERS ABOUT RISK FACTOR OF ASTHMA IN 1 TO 12 YEARS OLD CHILDREN - Sagheer Ahmad (Army Medical College Rawalpindi, 2018)
Objective: To determine the frequency of awareness in mothers about the risk factors of asthma in children aged 1-12 years, attending pediatric department, Combined Military Hospital, Quetta.